Intelligent Routing Scheme for Vehicle-to-Vehicle Communication - Sataraddi, Mamata J; Kakkasageri, Mahabaleshwar S (International Journal of Computer Sciences and Engineering, 2020)
Vehicle Ad Hoc Network (VANET) is a type of wireless network composed of vehicles and roadside communication devices. The main goal of VANET is to provide seamless communication for people travelling on the road to collect and relay information from all nearby vehicles in the event of emergency situations such as severe traffic jams, collisions, lane shift, speed limit, hazard or road condition alerts, position alert services and in the event of climatic disasters, etc. Due to high mobility of vehicles data transfer between vehicles in short period requires smart, intelligent routing algorithms. Proposed work aims at design of a intelligent agent (Belief-Desire-Intention) based routing for vehicle- to-vehicle (V2V) communication in VANETs. Intelligent routing scheme operates as follows: gathering of routing parameters, generation of beliefs, development of desires and finalization of route. Presented routing scheme is analyzed and compared with existing routing algorithm for VANETs known as M-AODV+ (Modified AODV+) with respect to packet delivery ratio, network life time and control overhead.